Technology and Higher Education: vision from the aesthetics to the human improvement - Varona Domínguez, Freddy (2023)
Abstract  This work is philosophical and is composed of two parts. The first, entitled Transformations in higher education due to the use of ICT, presents some of the alterations that have taken place in teachers and students, including the increase in the character of researcher and tutor in teachers, and the speed and diversity of apprenticeship mod. In the second part, under the title Aesthetics direct to the human improvement: perspective to use ICT in higher education, some theoretical elaborations are extended about aesthetics, human improvement and how the conjugation of these aspects constitutes a perspective from where the use of ICT in higher education can be observed; The center of these reflections is that in the face of the tendency to increase indifference, it is urgent to stimulate the sensitivity of students.